Malawi Economic Monitor, June 2021 : Investing in Digital Transformation - World Bank (World Bank, Lilongwe, 2021)
Malawi was affected by a severe second wave of COVID-19 (coronavirus) cases starting in the last weeks of 2020. As a result, the Government declared a second 'State of National Disaster' and announced increased social distancing measures. Case numbers peaked in January and gradually subsided through April, when restrictions were relaxed. Malawi received its first consignment of vaccination doses from COVAX in March, but uptake has been low, with around 400,000 doses administered to about 2 percent of the population as of mid-June. Growth in 2020 was strongly affected by the pandemic, falling to an estimated 0.8 percent, down from pre-pandemic projections of 4.8 percent. The pandemic’s impact on the services and industry sectors was partially offset by a strong agricultural harvest. Services and industry slumped amid the ongoing disruptions caused by the pandemic to global value chains and trade and logistics, decreases in tourism and remittances, and dampened demand due to social distancing measures. The accommodation and food services subsectors were the most affected, while information and communication services, and utilities performed well. Agricultural production estimates for 2021 are strong, but the pandemic will still weigh on economic activity. Maize production is expected to increase to 4.5 million tons, a 17 percent increase over 2020’s bumper harvest. Business sentiment is showing some improvement in early 2021 but is still below pre-pandemic levels. Some 46 percent of firms surveyed in February 2021 by the Malawi Confederation of Chambers of Commerce and Industry (MCCCI) expect a positive performance for the year. This is an improvement from 31 percent in 2020 but remains short of pre-pandemic levels.